Effects of Exercise on Parkinson’s Disease: A Meta-Analysis of Brain Imaging Studies - Li, Jingwen; Guo, Jian; Sun, Weijuan; Mei, Jinjin; Wang, Yiying; Zhang, Lihong; Zhang, Jianyun; Gao, Jing; Su, Kaiqi; Lv, Zhuan; Feng, Xiaodong; Li, Ruiqing (Frontiers in Human Neuroscience, 2022)
Background Exercise is increasingly recognized as a key component of Parkinson’s disease (PD) treatment strategies, but the underlying mechanism of how exercise affects PD is not yet fully understood. Objective The activation likelihood estimation (ALE) method is used to study the mechanism of exercise affecting PD, providing a theoretical basis for studying exercise and PD, and promoting the health of patients with PD. Methods Relevant keywords were searched on the PubMed, Cochrane Library, and Web of Science databases. Seven articles were finally included according to the screening criteria, with a total sample size of 97 individuals. Using the GingerALE 3.0.2 software, an ALE meta-analysis was performed using seven studies that met the requirements, and the probability of the cross-experiment activation of each voxel was calculated. Results The meta-analysis produced seven clusters, and major activations were found in the cerebellum, occipital lobe, parietal lobe, and frontal lobe brain regions. Conclusion Exercise for PD mainly results in the enhanced activation of the cerebellum, occipital lobe, parietal lobe, and frontal lobe. Exercise for PD does not cause a change in the activation of a single brain area, and the observed improvement may result from coordinated changes in multiple brain areas.